2020
DOI: 10.1017/ice.2020.266
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes of patients colonized with carbapenemase-producing and non–carbapenemase-producing carbapenem-resistant Enterobacteriaceae

Abstract: Objective: To compare risk factors and outcome of patients colonized with carbapenemase-producing (CP) carbapenem-resistant Enterobactereaceae (CRE) and non–CP-CRE. Design: A comparative historical study. Setting: A 1,000-bed tertiary-care university hospital. Patients: Adults with CP-CRE positive rectal swab cultures, non–CP-CRE positive rectal swab cultures, and negative rectal swab cultures (non-CRE). Methods: CP-CRE and non–CP-CRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The CCIS score of the CP-CRE group was higher than that of the non-CRE group in this study. In a study by Kassem et al [20] conducted in Israel, the CCIS score was significantly higher in the non-CP-CRE group than in the CP-CRE group, but multiple logistic regression analysis showed that CCIS was not related, which was consistent with the finding that it was not a risk factor for CP-CRE. CCIS is an index developed to predict the risk of death within one year of hospitalization based on the number of comorbidities and is often used to evaluate the prognosis or survival of patients [39].…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…The CCIS score of the CP-CRE group was higher than that of the non-CRE group in this study. In a study by Kassem et al [20] conducted in Israel, the CCIS score was significantly higher in the non-CP-CRE group than in the CP-CRE group, but multiple logistic regression analysis showed that CCIS was not related, which was consistent with the finding that it was not a risk factor for CP-CRE. CCIS is an index developed to predict the risk of death within one year of hospitalization based on the number of comorbidities and is often used to evaluate the prognosis or survival of patients [39].…”
Section: Discussionsupporting
confidence: 64%
“…CCIS is an index developed to predict the risk of death within one year of hospitalization based on the number of comorbidities and is often used to evaluate the prognosis or survival of patients [39]. Kassem et al [20] reported that as the CCIS score increased by 1 point, the in-hospital mortality rate increased by 1.09 times, indicating that CCIS reflects in-hospital mortality. The CCIS score has been reported to be related to increased mortality rates for the coronavirus disease in 2019 [40].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations